rhs gene family of Escherichia coli K-12. - Sadosky, A B (1989)
Two additional members of a novel Escherichia coli gene family, the rhs genes, have been cloned and characterized. The structures of these loci, rhsC and rhsD, have been compared with those of rhsA and rhsB. All four loci contain a homologous 3.7-kilobase-pair core. Sequence comparison of the first 300 nucleotides of the cores showed that rhsA, rhsB, and rhsC are closely related, with only 1 to 2% sequence divergence, whereas rhsD is 18% divergent from the others. The beginning of the core coincides with the initiation of an open reading frame that extends beyond the 300 nucleotides compared. Whether a protein product is produced from this open reading frame has not been established. However, nucleotide substitutions which differentiate the cores have highly conservative effects on the predicted protein products; this suggests that products are made from the open reading frame and are under severe selection. The four rhs loci have been placed on both the genetic and restriction maps of E. coli K-12. A fifth rhs locus remains to be characterized. In terms of size, number, and sequence conservation, the rhs genes make up one of the most significant repetitions in E. coli, comparable to the rRNA operons.